Interactive Case-Based Clinical Approach to the Painful Shoulder, Elbow, and Cervical Neck - Jane O'Rorke; Robert Quinn (Association of American Medical Colleges, 2015)
Abstract Introduction Musculoskeletal diseases were diagnosed in 18% of the 1.3 billion health care visits in the United States in 2011. Physicians from a variety of specialties will need skill in diagnosing and treating musculoskeletal disease. Medical students' lack of knowledge of and clinical confidence in the musculoskeletal system has been partially attributed to the fact that insufficient time is dedicated to musculoskeletal medicine. Of the 122 medical schools existing in the United States in 2003, less than 50% required preclinical courses in musculoskeletal medicine, less than 25% required a clinical course, and nearly 50% had no required course, preclinical or clinical. This module was designed to introduce over 200 second-year medical students to the clinical approach towards common upper extremity musculoskeletal complaints. It is innovative in its use of faculty from both primary care and orthopedic surgery. Methods The materials in this resource are for clinical faculty as they organize and present a learning session for preclerkship medical students on the clinical workup of shoulder pain, elbow pain, and wrist/hand pain. Ideally, an internist or family practitioner in combination with an orthopedic surgeon should present the session. The cases take the learner from initial presentation to surgical intervention. The resource material includes a list of questions for students to use in preparation for the session and a PowerPoint to be used by the faculty during the session. The PowerPoint has audience response questions, activities to be completed in pairs or individually, and videos. The material can be taught in a 3-hour session with two 10-minute breaks. Results Twenty-five percent of the class provided written evaluations of the session. Ninety-eight percent of those students agreed or strongly agreed that the session attained its goals. Students reported on the course evaluation that their confidence in assessing upper extremity complaints had increased. They felt more prepared to assess these issues in the clinical environment. In addition, the students have done very well on the musculoskeletal portion of the USMLE 2. Discussion This curriculum may be used with large groups of students and in schools where faculty resources may be limited. It covers a breadth of musculoskeletal medicine that may be seen initially in primary care or an acute care setting but subsequently need orthopedic surgery.